2020
DOI: 10.3390/antiox9020165
|View full text |Cite
|
Sign up to set email alerts
|

Plant Phenolics and Phenolic-Enriched Extracts as Antimicrobial Agents against Food-Contaminating Microorganisms

Abstract: Phenolic compounds and extracts with bioactive properties can be obtained from many kinds of plant materials. These natural substances have gained attention in the food research as possible growth inhibitors of foodborne pathogenic and spoilage bacteria. Many phenolic-enriched plant extracts and individual phenolics have promising anti-quorum sensing potential as well and can suppress the biofilm formation and toxin production of food-related pathogens. Various studies have shown that plant phenolics can subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(142 citation statements)
references
References 149 publications
2
112
0
1
Order By: Relevance
“…It is evident that among phytochemicals and other nutrients, polyphenolic compounds and ascorbic acid may be considered as the most valuable health beneficial constituents, which have been reported in various anatomical parts of Sorbus spp. The polyphenolics, which may influence the colour and flavour, have demonstrated antioxidant [54,81], antidiabetic [11,82] anti-hyperlipidemic [83], anti-inflammatory [84], antimicrobial [85], anticancer [86,87] antiviral [67], antifungal [79], antitumoral [88], anti-periodontal [89], and anti-osteoarthritis [90] effects, as well as vasoprotective [84], neuroprotective [26,91,92], cardioprotective [36], hepatoprotective [7], properties and COX-2 (cyclooxygenase-2) inhibitory [93] activities. Many of these activities are correlated to antioxidant capacity of bioactive compounds, which at cellular level may neutralize excessive reactive oxygen species, and thereby protect important biomolecules in the conditions of oxidative stress, which can cause cellular injury and development of chronic diseases.…”
Section: Promising Health Benefits and Related Applications In Foodsmentioning
confidence: 99%
“…It is evident that among phytochemicals and other nutrients, polyphenolic compounds and ascorbic acid may be considered as the most valuable health beneficial constituents, which have been reported in various anatomical parts of Sorbus spp. The polyphenolics, which may influence the colour and flavour, have demonstrated antioxidant [54,81], antidiabetic [11,82] anti-hyperlipidemic [83], anti-inflammatory [84], antimicrobial [85], anticancer [86,87] antiviral [67], antifungal [79], antitumoral [88], anti-periodontal [89], and anti-osteoarthritis [90] effects, as well as vasoprotective [84], neuroprotective [26,91,92], cardioprotective [36], hepatoprotective [7], properties and COX-2 (cyclooxygenase-2) inhibitory [93] activities. Many of these activities are correlated to antioxidant capacity of bioactive compounds, which at cellular level may neutralize excessive reactive oxygen species, and thereby protect important biomolecules in the conditions of oxidative stress, which can cause cellular injury and development of chronic diseases.…”
Section: Promising Health Benefits and Related Applications In Foodsmentioning
confidence: 99%
“…Another in vitro study reported the powerful bactericidal activity of broccoli sprouts against Helicobacter pylori by the presence of sulforaphane as the major anti-Helicobacter active compound, with highly active inhibition zones (>5 cm) [26]. Many reports showed that plant-derived bioactive compounds, such as phenolics, flavonoids, and glucosinolates, can inhibit the growth and activity of various microorganisms [110]. With the diversity in the molecular structure and chemical composition, these compounds can perform distinct antimicrobial effects, such as destabilization of the plasma membrane or inhibition of extracellular enzymes [110].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Many reports showed that plant-derived bioactive compounds, such as phenolics, flavonoids, and glucosinolates, can inhibit the growth and activity of various microorganisms [110]. With the diversity in the molecular structure and chemical composition, these compounds can perform distinct antimicrobial effects, such as destabilization of the plasma membrane or inhibition of extracellular enzymes [110]. The antimicrobial activity against pathogenic bacteria, yeast, and phytopathogenic fungi was also proven by the presence of many antimicrobial peptides in broccoli floret extract [111].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Extracts from Tetradium ruticarpum (synonym: Evodia ruticarpa; skunk ash) containing quinolinones and indole quinazoline alkaloids were also able to attenuate virulence factors in C. jejuni (Bezek et al 2016). In general, phenolic compounds such as flavonoids, tannins and lignans, and phenolic plant extracts have an antimicrobial effect; thus, biofilm and toxin formation can be reduced by their anti-qs activity (Takó et al 2020).…”
Section: Natural Products and Plant Extracts Against Campylobactermentioning
confidence: 99%